2011
DOI: 10.1007/s12613-011-0498-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of long alumina fibers by sol-gel method using tartaric acid

Abstract: Long alumina fibers were prepared by sol-gel method. The spinning sol was obtained by mixing aluminum nitrate, tartaric acid, and polyvinylpyrrolidone with a mass ratio of 10:3:1.5. Thermogravimetry-differential scanning calorimetry (TG-DSC), Fourier transform infrared (FT-IR) spectra, X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to characterize the properties of the gel and ceramic fibers. A little of α-Al 2 O 3 phase is observed in the alumina precursor gel fibers sintered at 127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was shown that the aluminum powder had the highest solubility at 95 ℃, and a colorless and transparent alumina sol with the highest solid content was obtained; the spinning sol was best spinnable when the molar ratio of formic acid to acetic acid was 1.15:0.85. Tan Hongbin`s group [12,[17][18] used tartaric acid, malic acid and lactic acid separately to react with aluminum nitrate and get ACs. When the mass ratio of aluminum nitrate: organic acid was 10:3, the sol spinning performance was the best.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the aluminum powder had the highest solubility at 95 ℃, and a colorless and transparent alumina sol with the highest solid content was obtained; the spinning sol was best spinnable when the molar ratio of formic acid to acetic acid was 1.15:0.85. Tan Hongbin`s group [12,[17][18] used tartaric acid, malic acid and lactic acid separately to react with aluminum nitrate and get ACs. When the mass ratio of aluminum nitrate: organic acid was 10:3, the sol spinning performance was the best.…”
Section: Introductionmentioning
confidence: 99%